PARTISIPASI MASYARAKAT DALAM PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DI KELURAHAN PARUNG JAYA KECAMATAN KARANG TENGAH KOTA TANGERANG - Maulana, Muhammad Iqbal; Gustiana, Rachmat; Suwandi, Suwandi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The main problem in this study is whether the development planning carried out in Parung Jaya Village, Karang Tengah District, Tangerang City has been based on community participation, and aims to determine community participation in development planning in Parung Jaya Village, Karang Tengah District, Tangerang City. In this study using qualitative research methodology through the process of interview and observation. Interviews are conducted by way of direct questioning and answering to informants. The findings of this study are from indicators of community participation in village development planning at the assessment stage, alternative planning stage, program implementation stage, and evaluation stage. The results of the study are that at the assessment stage, it can be said that community participation can be said to be good, namely the community has been sensitive to the phenomena and realities that are happening around them. At the alternative planning stage, the program explores in-depth ideas by involving the community as a whole so that all community needs can be accommodated. At the implementation stage, it can be said that the government has succeeded in increasing public participation. At the stage of community evaluation of the government in the implementation of development has been very good, they participate in enjoying and maintaining the results of development